Relationship between Reflection Coefficient and Moisture Content of Oil Palm Fruit Using an Open-Ended Rectangular Waveguide Technique - Ali, Adib (2007)
The thesis describes the development of an open-ended waveguide technique for the determination ofof complex permittivity and moisture content of the oil palm fruits of various degree of fruit ripeness. The operating frequency of the waveguide operate betweenwas between 8 GHz and 12 GHz. A theoretical analysis has beenncarried out to determine the relationship between reflection coefficient, frequency and moisture content in the oil palm fruit. The propagation of electromagnetic wave is assumed to be transverse electric (TZE) mode. The measurement system consists of thea standard waveguide and a PC-controlled vector network analyzer (VNA). Dielectric measurement software A computer program has been developed to control and acquire reflection data from the VNA using Agilent VEE at each 201 frequency points between 8 GHz and 12 GHz. Comparison results between calculated and measured reflection coefficient are presented. A calibration equation relating the measured and predicted moisture content has been established based on more than 1500 fruit samples. The actual moisture content werewas found determineddetermining by standard oven drying method. The calibration equation was found to be accurate within ± 5 % when tested on 50 different fruit samples which each biker have 30 fruits with same moisture content.of various moisture contents.